PENGGUNAAN VITAMIN E DAN BHT DALAM PENGENCER SEMEN BEKU DOMBA - Feradis Feradis (State Islamic University of Sultan Syarif Kasim Riau, 2010)
A study about the use ofvitamin E and BHT in frozen ram senten extender has done. Tris citrate, lactose and skim milk as extenders and vitamin Eand BHT as antioxidants with ceitain doses were used in this experiment. The quality ofsemen such as motility, live sperm, intact plasma membrane and intact acrosom membrane were evaluated. The objectives ofthis study are to determine the best extender and antioxidant with certain doses in cryopreservation of ram semen. Based on